Facilitators and Barriers to adherence to antiretroviral therapy among incarcerated people living with HIV in Iran: insights from a qualitative study - Azam Bazrafshan; Ali Ahmad Rafiei-Rad; Maliheh Sadat Bazrafshan; Nima Ghalekhani; Soheil Mehmandoost; SeyedAhmad SeyedAlinaghi; Fatemeh Mehrabi; Mehrdad Khezri; Gelareh Mostashari; Mohammad Karamouzian; Hamid Sharifi (Harm Reduction Journal)
Abstract Background Ensuring consistent adherence to antiretroviral therapy (ART) is crucial for effective HIV treatment and achieving viral suppression. Within prisons, the prevalence of HIV is notably high, and incarcerated individuals face an increased risk of transmitting the virus both during and after incarceration. However, facilitators and barriers to ART adherence among these individuals in low- and middle-income countries remain inadequately explored. This study applied the Social Ecological Model (SEM) to investigate how various individual, interpersonal, organizational, community and policy-level factors impact ART adherence among incarcerated populations in Iran during and post-incarceration. Methods This study employed a phenomenological qualitative approach using semi-structured interviews to gather insights. The research population consisted of people living with HIV (PLHIV) who had experienced incarceration and had been prescribed ART during their latest incarceration. Eleven PLHIV from two prisons located in Kerman and Tehran, Iran, formed the study group. Qualitative findings from the interviews were analyzed using a thematic approach. The findings were organized within the SEM framework to highlight key themes influencing ART adherence during and after incarceration. Results Participants had an average age of 45.1 years (± 5.6). Various factors influence ART adherence during and post-incarceration. Participants highlighted the individual (e.g., HIV knowledge, previous treatment history, mental and physical health), interpersonal (e.g., family, friends, other incarcerated people, and prison health staff), organizational (e.g., ART treatment interventions, methadone maintenance therapy, and other health protocols), community (e.g., stigma, social isolation, discrimination and lack of access to community health services), and policy (e.g., financial interventions, and providing shelters) level factors influence ART adherence during and post-incarceration. Conclusions This study provides insights into the multi-level approach to ART adherence among PLHIV during and post-incarceration. It recommends implementing public health activities at the proposed multi-levels to maximize the synergies of intervention for the greatest impact.